Potensi Budaya Dan Tradisi Desa Wisata Umauta Sebagai Daya Tarik Wisata Di Kabupaten Sikka - Natalia Kristiani Tandafatu; Michael Rudolfus Sawu; Desiderius Siga Meli Poa (Jurnal Projemen UNIPA, 2025)
Umauta Tourism Village has an art and cultural studio called Doka Tawa Tana, which specializes in handcrafted art involving motif-tying with threads that are then processed into sarong cloth for daily use or sale to meet family economic needs and social community needs. The Doka Tawa Tana Studio serves as a place for learning local wisdom values for the community and the younger generation. This research aims to identify and analyze the cultural and traditional potential of Umauta Village as a tourist attraction in Sikka Regency. The method used in this research is a qualitative descriptive approach. The findings of this study conclude that Umauta Tourism Village is not only a tourist destination but also a center for cultural preservation involving the community and attracting both local and international tourists. By continuously developing its artistic and traditional potential, Umauta Tourism Village has become a successful example of sustainable community-based tourism.